A guide for co-designing an inclusive landscape management plan - Tilahun, Seifu A.; Atampugre, Gerald; Zemadim, Birhanu; Cofie, Olufunke O.; Mabhaudhi, T. (International Water Management Institute (IWMI). CGIAR Initiative on West and Central African Food Systems Transformation, 2023)
This technical note outlines a framework for the co-design of inclusive landscape management plans (ILMPs) by local governments and other implementers. The co-design process is iterative, incorporating the perspectives of all stakeholders, piloting, and learning through monitoring, and evaluation. The framework ensures that the co-signed ILMPs are adaptive, one health-sensitive, promote sustainable intensification, and are embedded in local and national governance systems.